Peningkatan Keterampilan Manajemen Bisnis Online bagi UMKM Desa Olean - Jannah, Raudatul; Mukminin, Amirul; Yaqin, Ainul; Faridah, Lia; Umam, Khotibul (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Digitalization has become a crucial need in the development of Micro, Small, and Medium Enterprises (MSMEs), especially in improving market access and business legality. In Olean Village, Situbondo Regency, most MSME actors lack digital skills and formal legal documents such as Business Identification Numbers (NIB) and halal certification. This community service aimed to enhance online business management skills through training on social media utilization, Google Maps registration, and SWOT analysis. The method involved needs assessment, coordination with local authorities, offline training, and two weeks of online mentoring. The results showed a significant improvement in participants’ digital skills and the formation of the "UMKM Digital Olean" community as a platform for collaboration and sharing best practices. This program demonstrates that a community-based approach is effective in empowering MSMEs sustainably in rural areas.